Science is as science does: aligning teaching philosophy, objectives, and assessment - Krehbiel, Matthew D. (Kansas State University, 2006)
In the current high-stakes assessment environment of NCLB and AYP, the type of assessment students are subject to is crucial. Good assessments make teaching to the test an effective, rather than deplorable, strategy that aligns learning objectives, classroom teaching, and student achievement. While science, this author’s content area, isn’t currently AYP mandated, it will be soon, and in the meantime, students are still required to take state and local assessments. This project seeks to effect change on a local level – specifically, with how the local CRT is written so that it can both reflect sound research-based assessment practice as well as an understanding of science as concept- and process-based rather than content- and fact-based.
Keywords: Assessment; Science education; Curriculum alignment; NCLB; Education, Sciences (0714)